Social and socio-psychological peculiarities of adolescent aggression in modern Russian society: regional aspect - V. V. Levchenko (Вестник университета)
Urgent problems of adolescent aggression as an integral part of deviant behavior, which often manifests itselfprecisely in the adolescent complex "transitional" period of human development, which is very often accompanied by various negative manifestations of personality disharmony (including aggressiveness), requiring constant detailed and deep attention and analysis, since there is a danger that the aggression of adolescents can go into adulthood, turn from a social pathology into a social norm, have been considered. Based on a comprehensive theoretical analysis and consideration of the results of empirical research aimed at studying the social and socio-psychological aspects of adolescent aggression, the well-reasoned patterns of the structure of adolescent aggression of schoolchildren of the Perm Territory, the prevailing forms of their aggression have been highlighted and described. Factors influencing the overall the level of aggression and on the types of aggression, as well as the influence of aggression on the assessment of life success and well-being in schoolchildren, have been identified and analysed.